Project-Based Learning in Creative Writing: Teachers' Strategies and Encountered Obstacles - Muhammad Randy Sultan; Nur Qalbi; Syamsiarna Nappu (Universitas Hamzanwadi, 2023)
Project-Based Learning (PjBL) emerges as a pivotal approach in modern pedagogy. This research delves into how English teachers at the eleventh-grade level in SMA Dunia Harapan Makassar integrate PjBL in their creative writing curriculum, the challenges faced during this implementation, and its impact on students' writing outcomes. Utilizing a mixed-method approach, data was sourced from observation checklists, teacher interviews, and students' creative writing samples. Findings revealed both participating teachers proficiently applied PjBL syntaxes and began instruction by discussing linguistic elements of short stories. Challenges emerged in time management, sparking student enthusiasm for writing, and aligning PjBL with the Cambridge A-level curriculum and the CCP framework, emphasizing character development, communication, and problem-solving. A review of students' writings showed commendable results; organization, vocabulary, grammar, and mechanics achieved average scores of 19.25, 18.87, 22.37, and 4.5 respectively. Content scored an average of 25.12, denoting good quality. Despite specific hurdles, the study underscores that with adept PjBL integration, students can markedly improve their creative writing prowess.